Local excision versus thrombectomy in thrombosed external hemorrhoids: a multicenter, prospective, observational study - Ali Yalcinkaya; Ahmet Yalcinkaya; Semra Demirli Atici; Can Sahin; Sezai Leventoglu; on behalf of T E H Study Collaboration (BMC Surgery, 2023)
Abstract Background Available guidelines describing the procedural treatment of thrombosed external hemorrhoids (TEH) rely solely on expert opinion. We aimed to compare local excision (LE) and thrombectomy (incision) in terms of treatment success, factors affecting success, and outcomes. Methods This was a multicenter, prospective, observational study conducted in eight centers from September 2020 to September 2021. A total of 96 patients (58 LE, 38 thrombectomy) were included. Risk factors, demographics and clinical characteristics were recorded. Follow-up studies were scheduled for the 1st week, 1st, 3rd and 6th months. Surgical success was assessed at 1 month. Hemorrhoidal Disease Symptom Score (HDSS) and Short Health Scale (SHS) were applied at baseline and the 6th month. Wexner fecal incontinence score was applied at all follow-up studies. Results Overall mean age was 41.5 ± 12.7 years. At baseline, groups were similar with regard to demographics and disease severity (HDSS) (p > 0.05 for all). Success was relatively higher in the thrombectomy group (86.8%) compared to the LE group (67.2%) (p = 0.054). Constipation and travel history were significantly associated with lower likelihood of LE success. Symptoms during follow-up were similarly distributed in the groups. Both methods yielded significant improvements in HDSS, SHS and Wexner scores; however, SHS scores (6 months) and Wexner scores (all time points) were significantly better in the thrombectomy group. Conclusion The in-office thrombectomy procedure may have better short-term outcomes compared to LE in terms of relative success, recurrence and quality of life–despite the fact that success rates were statistically similar with the two interventions. LE may yield particularly worse results in patients with constipation and travel history; thus, thrombectomy appears to be especially advantageous in these patient subsets.